The Cpx two-component signal transduction pathway is activated in Escherichia coli mutant strains lacking phosphatidylethanolamine. - Mileykovskaya, E (1997)
The CpxA-CpxR two-component signal transduction pathway of Escherichia coli was studied in a mutant (pss-93) lacking phosphatidylethanolamine (PE). Several properties of this mutant are comparable to phenotypes of cpxA point mutants, indicating that this two-component pathway is activated in PE-deficient cells. In contrast to point mutants, cpx operon null mutants have a wild-type phenotype. By use of this information, a cpx operon null allele was introduced into a pss-93 mutant. Certain altered properties of PE-deficient mutants, which were consistent with activation of the Cpx pathway, returned to the wild-type phenotype, namely, active accumulation of proline and thiomethyl-beta-D-galactopyranoside was partially restored to wild-type levels, increased resistance to amikacin returned to wild-type sensitivity, and high levels of degP expression returned to repressed wild-type levels. Elevated levels of acetyl phosphate and nlpE gene product can result in activation of the Cpx pathway. However, inactivation of the nlpE gene or mutations eliminating the ability to make acetyl phosphate did not alter the high level of degP expression in pss-93 mutants. We propose that the lack of PE results in an alteration in cell envelope structure or physical properties, leading to direct activation of the Cpx pathway.